Corporate Growth and CEO Compensation: Case from Indonesia - lindrianasari lindrianasari; Jogiyanto Hartono; SUPRIYADI SUPRIYADI; SETIYONO MIHARJO (The Indonesian Journal of Accounting Research, 2013)
This study aims to obtain empirical evidence on whether   corporate growth affects the amount of compensation received by CEOs in Indonesia. The contribution of this study is to provide emporical   evidence on how CEOs perceive their level of compensation when they succeeded in increasing the value of the firm. The samples are 395 firm-year from 2005-2008. Test results show that growth has a positive relationship with the amount of compensation received by the CEO in Indonesia. Net income and total assets are significantly related to the amount of compensation received by CEOs, while stock price is not.